(untitled) (Global Journal of Science Frontier Research, 2018)
Agriculture plays a very important role in Ghana and Africa at large. It’s a source of income and sustenance for the large majority of Ghanaians. Recently, there have been huge drawbacks in the development of the agricultural sector in the country due to incidents of drought most profoundly in the northern region, which has led to the deterioration of several farmlands. This has directly and indirectly affected the lives of many, most especially those who depend on it for a living. This project is thus developed with the main objective of helping to address the issues of crop destruction due to the inability of farmers to store water in the rainy season and use it later on when there is not much water or lack of rainfall. The proposed system would address this challenge by having a water tank, which would store the water to be used for irrigation. The system would then have a soil moisture sensor in the soil, to measure the amount of water in the soil. If the water in the soil falls below a preset threshold for the farmland, the system would automatically irrigate that portion of the farm to keep the soil in good condition. This system is achieved by the use of a PIC16F887A microcontroller, which is connected to the soil moisture sensor, which takes the readings for the microcontroller. The microcontroller upon receiving the soil moisture readings from the soil moisture sensor would display the readings on an LCD and if the soil is in good condition the system performs no action, but if the soil is dry, the water pump is activated to pump water for the purposes of irrigating the soil.